Pesticide residue in commonly consumed vegetables in selected districts of Jimma Zone, Southwest Ethiopia - Hawi Hussen Ahimed; Higemengist Astatkie; Seblework Mekonen; Fitsum Demissie; Samuel Fekadu (PLoS ONE, 2026)
Background Pesticides are essential in agriculture for protecting crops from pests, diseases, and weeds, but improper use can lead to health issues like neurological disorders and carcinogenic effects. Strengthening regulatory frameworks, promoting integrated pest management strategies, and raising farmer awareness can mitigate pesticide misuse. In Ethiopia, widespread pesticide use in vegetables raises concerns about consumer exposure to pesticide residues. This study determined the pesticide residue in vegetables in Southwest Ethiopia. Methods The study was conducted in randomly selected districts of the Jimma zone. Samples of tomatoes, potatoes, cabbage, and onions were collected from vegetable farmers. The modified QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) methods were used for sample preparation and extraction. The analysis of pesticide residues was performed using gas chromatography coupled with a mass spectrometer (GC-MS) and an ion trap analyzer with an automatic injection. The pesticide detection levels among types of vegetables and locations were analyzed using one-way Analysis of variance (ANOVA) with statistical significance set at p < 0.05. Results Pesticide residues were detected in vegetables from Seka Chokorsa, Goma, and Dedo districts. Detected pesticides include Lindane, Aldrin, Chlorpyrifos, 4,4-DDE, Hexachlorobenzene, and Endosulfan II. The highest concentrations were found in the Dabo Gibe onion sample (Seka Chokorsa), the Waro Kolobo potato sample (Dedo), and the Ganji Dalacho cabbage sample (Goma). Lindane residues were found in onion and potato (Seka Chokorsa), exceeding the Maximum Residue Limit (MRL) of 10–50 µg/kg. Chlorpyrifos residues were detected below MRLs across all districts, while 4,4-DDE residues were also detected in some vegetables, indicating historical use of banned pesticides. ANOVA results showed small variation between groups, and there was no statistically significant difference across the four groups (p-value = 0.305). The study highlights the need for stricter regulation, farmer education, and residue monitoring to ensure food safety.